Application of calcium and boron directed to inflorescences in production, quality and nutrient accumulation in lettuce seeds - Bezerra, Sara Raissa B. [UNESP]; Marques, Isabella B. [UNESP]; Bardiviesso, Estefânia M. [UNESP]; Pelvine, Raíra A. [UNESP]; Aguilar, Ariel S. [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP] (FapUNIFESP (SciELO), 2023)
Calcium and boron are important nutrients in the stages of flowering, pollen germination and in the fruiting process. As these nutrients are poorly mobile in the plant, some authors recommend foliar spraying in the production of seeds of some species. The objective was to study the influence of calcium and boron, via application directed to inflorescences, in production, quality and accumulation of nutrients in lettuce seeds. Four treatments were evaluated (only calcium: 0.72 g/L; only boron: 0.17 g/L; joint application of calcium and boron and control), in randomized blocks design with six replications. No influence was obtained between the treatments for seed production (number and weight of seeds per plant). Using boron, alone or together with calcium, the weight of a thousand seeds was lower compared to control, while only calcium did not differ from the control. No differences were obtained for germination and seed vigor. The application of calcium did not affect the accumulation of nutrients, however boron application increased the accumulation of this nutrient in the seeds. The application of calcium and boron directly in the inflorescences of lettuce did not promote an increase in the production and vigor of the seeds.
Produção, qualidade e acúmulo de nutrientes em sementes de alface com aplicação de cálcio e boro direcionada às inflorescências
Keywords: foliar fertilization; germination; Lactuca sativa; seed physiological potential; vigor